The Interplay of Goalkeepers and Penalty Takers Affects Their Chances of Success - Noël, Benjamin; van der Kamp, John; Klatt, Stefanie (Frontiers in Psychology, 2021)
Research in penalty kicking has primarily focused on spatial decision making, while temporal decision making has largely been neglected, even though it is as critical for success. Temporal decision making concerns goalkeepers choosing when to initiate their jump to the ball during the penalty taker’s run-up (i.e., jump early or wait long), and penalty takers deciding where to kick the ball, either prior to the run-up or after the goalkeeper has committed to one side. We analyzed penalty takers’ and goalkeepers’ behavior during penalty shoot-outs at FIFA World Cups and UEFA European Championships to scrutinize if temporal aspects of decision making have an impact on penalty kick success. Results indicate that the likelihood of a penalty kick being scored depends on the combination of penalty takers’ and goalkeepers’ temporal decision-making strategies. Hence, moving early more often seems fruitful for goalkeepers, while penalty takers should consider varying penalty kick strategy between attempts.